Bargaining and Competition Part I: Characterization - Gale, Douglas (Econometrica, 1986)
[A model of decentralized exchange and price formation is defined using the bargaining theory of A. Rubinstein. Agents meet at random and bargain over the terms of trade. If there are no transaction costs, every perfect equilibrium of the bargaining game implements a Walrasian equilibrium of the underlying exchange economy.]